Genetics of monogenic diabetes: Present clinical challenges - Misra, S; Owen, KR (Springer Science and Business Media LLC, 2018)
Purpose of Review Monogenic forms of diabetes have specific treatments that differ from the standard care provided for type 1 and type 2 diabetes, making the appropriate diagnosis essential. In this review, we discuss current clinical challenges that remain, including improving case-finding strategies, particularly those that have transethnic applicability, and understanding the interpretation of genetic variants as pathogenic, with clinically meaningful impacts.